PRESENTASI DIRI SEORANG INTEL DI SAT INTELKAM POLRES KABUPATEN ROKAN HILIR (ROHIL) DALAM PENGUNGKAPAN KASUS PENCURIAN - Elvia Febriani; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The Presentation of self is an activity undertaken by individuals to foster the impression to others suit the individual. Percentage themselves usually done by people with certain professions such as intelligence. Intelligence serves as a case investigator must present themselves well to the criminals and the people. This is done so in the disclosure of criminal cases such as theft is often the case in Rokan Hilir can be resolved quickly and appropriately. When performing themselves, an intelligence has the front stage as a member of an undercover police to investigate the case and the back stage as a person who is. Two of stage is contained in Dramaturgy theory popularized by Goffman. This study aims to determine the front stage and back stage an intelligence on Sat Intelkam Polres district Rokan Hilir in spy case of theft.This study used qualitative research methods. Subjects in this study were three members of the intelligence on Sat Intelkam Polres Rokan Hilir on social and cultural part that went to the field to catch the suspect. Data collection techniques are grouped through participant observation, in-depth interviews, and documentation. This study uses data analysis interactive model of Miles and Hubermen, using a technique that checks the validity of the data through the extension of participation and triangulation.These results indicate that an intelligence must manage impression by changing the font settings and personal while they are at the front stage this is done so that people are not suspicious of their presence when the disclosure of theft . Setting is setting a place , time and atmosphere of the time of the drama , while personal font is a tool that brought current and body language displayed during the staging of the drama . Each intelligence has its own role that has been prepared in the back of the stage , a role performed in accordance with karater they wish to show the time in front of the stage . On the back of the stage ( back stage ) remains a human intelligence that is in accordance with their personality when in the family and closest friends . Because in the back stage ( back stage ) intel interact with the environment created for the closest fit without intelligence as well as social beings .Keywords: Self-presentation, Intelligence, Dramaturgy, Front Stage, Back Stage